PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA SEKOLAH BISNIS DI SURAKARTA - Sari, Dian Saptorini Putri Indah; Istiyanto, Budi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
This study aims to determine and analyze the effect of service quality consisting of tangibles, empathy, reliability, responsiveness and assurance variables on student satisfaction from a business school in Surakarta partially and simultaneously. The population in this study were students of STIE Surakarta consisting of accounting and management study programs with categories of morning class, evening class and also alumni. The number of samples using the slovin formula is 96 respondents using non-probability sampling method. The analytical method used is descriptive analysis and multiple regression analysis using the SPSS 21 program. The results of the study show that partially the reliability and assurance service quality variables have a significant effect on student satisfaction at STIE Surakarta, while tangibles, empathy and responsiveness variables have no significant effect on satisfaction. STIE Surakarta students. And the results simultaneously show that service quality significantly influences student satisfaction at STIE Surakarta.